Enhancement of Web Security Against External Attack - Md. Fazlul Haque; Mohammad Badrul Alam Miah; Fuyad Al Masud (European Scientific Journal, ESJ, 2017)
The security of web-based services is currently playing a vital role for the software industry. In recent years, many technologies and standards have emerged in order to handle the security issues related to web services. This paper shows techniques to enhance the security of web services, and some of the recent challenges and recommendations of a proposed model to secure web services. It shows the security process of a real life web application, which includes; HTML5 forms, login security, and a single signon solution. This paper also aim to discuss the ten (10) most common web security vulnerabilities and how to prevent the web application from three (3) of the vulnerabilities. Amongst them are; SQL Injection, Cross Site Scripting and Broken Authentication, and Session Management.